Influence of Graphene Oxide Incorporation on Temperature, Slump, Air Content, Specific Gravity, and Compressive Strength of Concrete at 7 and 28 Days - Nuñez, Bryan (2024)
In recent years, graphene oxide has become one of the most innovative and promising nanomaterials for civil engineering studies. Despite its potential benefits, the effects of graphene oxide on concrete properties have not been extensively studied. In the research, an experimental study was carried out to evaluate the impact of different doses of graphene oxide (0.08%, 0.10%, and 0.12% by weight of cement) on the compressive strength of concrete and the properties of fresh concrete (Temperature, Settlement, Unit Weight, Air Content). The evaluation was carried out both after 7 and 28 days of concrete curing. The results obtained in the research indicate that, of the doses tested, the mixture containing 0.08% graphene oxide is the most effective in improving the compressive strength of concrete after 7 days, while at 28 days the dose of 0.10% GO is the most appropriate since it achieved a higher compressive strength of the concrete. In addition, the favorable cool properties of concrete are preserved at the same time.